Risk management for events - Silvers, Julia Rutherford; O'Toole, William, 1951- (Abingdon, Oxon ; New York : Routledge, 2021)
"Risk Management for Events is a comprehensive and practical guide which supports academic and professional development programs to prepare individuals for entering or advancement in the international events industry. Events of all types are produced every day for all manner of purposes, attracting all sorts of people. Creating and managing the environment in which these people will gather carries with it awesome responsibilities - legal, ethical, and financial. To provide a safe and secure setting and to operate in a manner that ensures the hosting organizations or individuals achieve their objectives in a proper and profitable way, event risk management must be fully integrated into all event plans and throughout the event management process. This new edition has been revised and updated to include: New case studies and examples from a wide range of international destinations and different types of events. Updated statistics and data throughout. New content on emergent risk, onsite decision making, terrorism, public health including the covid-19 pandemic, and corruption within events. Updated online material including a case study archive and weblinks to useful resources. This will be an invaluable resource for all those studying events management"--
Revised edition of: Risk management for meetings and events, c2015.
Includes bibliographical references and index.
Keywords: Special events -- Management -- Study and teaching; Special events -- Safety measures; Special events -- Safety measures -- Case studies; Special events -- Planning; Special events -- Planning -- Case studies; Risk management